Romanian old Mass-Media – the mirror to our historical and cultural past (Confluenţe Bibliologice, 2026)
The article reﬂects the research work of documentary heritage (preserved in old documents) from the rare book collection of the Scientiﬁc Library of the „Alecu Russo" State University of Balti. A series of articles highlights with topics from all areas of human knowledge published in the pages of magazines from the 1930s: Viaţa Românească, Revista Fundaţiilor Regale, Convorbiri literare, Boabe de grîu, Cuget Clar etc.. These magazines (the rich and valuable content) marked an important moment in the evolution and aﬃrmation of national culture, contributed to the promotion of the values of the inter-war literature.
Keywords: Rare periodical publications collection; Boabe de Grâu magazine; religious magazines